Prevalence of diabetes among patients and the assessment of the awareness of the bidirectional relation between diabetes and periodontal disease - Anisha A Mahtani; Caroline Jacob; Reema Lakshmanan (Journal of Family Medicine and Primary Care, 2020)
Aim: To assess the extent of self-awareness and knowledge of diabetes and its association with periodontal disease among patients seeking dental care. Materials and Methods: Data were collected in the form of a questionnaire from 150 consecutive adult patients from the outpatient department of Saveetha Dental College in Chennai, India. Complying patients were tested for diabetes mellitus by checking their random blood sugar and the results were correlated with the questionnaire and their periodontal findings. The findings were interpreted to examine the relationship between self-awareness and clinically diagnosed periodontitis. Results: One hundred fifty patients participated in the questionnaire and 70% were unaware of diabetes causing periodontal disease. A total of 47.3% of patients were also unwilling to get themselves tested for diabetes by their dentists as nearly 73.3% believed that they did not have diabetes. As a result, out of 150 patients, 41 consented to random blood sugar but only 23 patients followed up. Among these 23, 14 believed they were diabetic but only 12 of those 14 were proven to be so. Additionally, 20 patients were diagnosed with either localized or generalized chronic periodontitis while the remaining 3 patients had gingivitis. All 12 patients diagnosed with diabetes were affected by periodontitis as well. Conclusions: Patients are generally apprehensive and misinformed regarding the influence of periodontitis and diabetes between both diseases and must be educated by both the medical and dental practitioners regarding the implications of these chronic inflammatory diseases.